2020
DOI: 10.1155/2020/7928961
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial Comparing Short versus Prolonged Hemostasis with Rescue Recanalization by Ipsilateral Ulnar Artery Compression: Impact on Radial Artery Occlusion—The RESCUE-RAO Trial

Abstract: Background. Despite the enormous benefits of radial access, this route is associated with a risk of radial artery occlusion (RAO). Objective. We compared the incidence of RAO in patients undergoing transradial coronary angiography and intervention after short versus prolonged hemostasis protocol. Also we assessed the efficacy of rescue 1-hour ipsilateral ulnar artery compression if RAO was observed after hemostasis. Material and Methods. Patients referred for elective transradial coronary procedures were eligi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
1
0
4
Order By: Relevance
“…A study reported that while hand swelling and radial artery hemorrhage fully resolve after medical treatment and sheath removal, RAO is the most common postprocedural complication, and approximately half of the cases eventually experience spontaneous recanalization [24]. Larger forearm artery [25], shorter compression time, small sheath size, higher dose of anticoagulation, vasorelaxing regimen, and distal radial artery approach have been recognized in several studies as an effective way to prevent RAO [26][27][28]. However, recent research indicated that sheath size and compression time do not affect short-term or long-term incidences of RAO following TRA [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…A study reported that while hand swelling and radial artery hemorrhage fully resolve after medical treatment and sheath removal, RAO is the most common postprocedural complication, and approximately half of the cases eventually experience spontaneous recanalization [24]. Larger forearm artery [25], shorter compression time, small sheath size, higher dose of anticoagulation, vasorelaxing regimen, and distal radial artery approach have been recognized in several studies as an effective way to prevent RAO [26][27][28]. However, recent research indicated that sheath size and compression time do not affect short-term or long-term incidences of RAO following TRA [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Частота ОЛА при коротком гемостазе была 1,4%, при пролонгированном 10,2%, в общей популяции 21,8% (p<0,001). Аналогичные результаты были получены авторами других исследований, в которых в зависимости от методики гемостаза час тота ОЛА варьировалась от 1,1 до 33% [1,3,[8][9][10]. Высокая частота ОЛА в ретроспективном исследовании хорошо соотносится с 30% частотой у Uhlemann M, et al, которые показали реальную клиническую практику, включив всех врачей и пациентов в исследование [11].…”
Section: материал и методыunclassified
“…В отличие от других исследований, наша работа включает всех пациентов, подлежащих чрескожному вмешательству, без рафинированных выборок. Кроме этого, высокую частоту окклюзии можно объяснить частым использованием УЗИ для подтверждения ОЛА, в сравнении с предыдущими работами, в которых УЗИ используется спорадически или не используется вовсе [1,3,[8][9][10]. Клиническая значимость ОЛА требует достоверного её определения с помощью УЗИ или теста Барбо с пульсоксиметром.…”
Section: материал и методыunclassified
See 1 more Smart Citation
“…O fato de a via radial ter se transformado na via de escolha para os PCP e seu potencial risco para OAR após procedimento incentivaram a busca de estratégias para sua prevenção. Entre as estratégias mecânicas cientificamente comprovadas estão o tempo de compressão hemostática mais curto 27 , a hemostasia patente 28 , e a compressão conjunta da artéria ulnar com a hemostasia patente 29 . Entre as estratégias farmacológicas citam-se o uso intrarterial na artéria radial de heparina não fracionada, de baixo peso molecular e inibidores diretos da trombina (bivalirudina) 22 , assim como a injeção subcutânea de nitroglicerina (NTG) 19 .…”
Section: Introductionunclassified